CHARACTER EDUCATION MANAGEMENT IN THE SOCIETY 5.0 ERA AT THE INTEGRATED MADRASAH IBTIDAIYAH TAHFIZHUL QUR'AN AL-MA'SHUM (MITTQUM) SURAKARTA - Elya Umi Hanik; Alya Nailul Karima; Fella Suffah; Puspita Masruroh (Fakultas Agama Islam Universitas Billfath, 2023)
The purpose of this study is to find out how the management of character education is in the era of society 5.0 at the Integrated MI Tahfizhul Qur'an Al-Ma'shum Surakarta. This research is a qualitative research that uses a descriptive approach. Collecting research data using interview techniques, observation and documentation. The data analysis used consisted of data reduction, data presentation and verification. The results of this research are that the management of character education in the era of society 5.0 at MITTQUM Surakarta has been going well through planning, teaching, implementing, and supervising. Instilling values ​​in building character education in the era of society 5.0 at MITTQUM is by habituating and forming the personality and good character of students. Character education planning activities include incorporating character education values ​​into the learning contained in the lesson plans for each formal subject, habituating the practice of carrying out Dhuha and Dhuhur prayers in congregation every day. In character education in the era of society 5.0 at MITTQUM Surakarta, teachers must continue to encourage and show examples to their students. This will ensure that character education in today's era is applied in everyday life until students mature.